Unusual method of creation of a transcatheter fenestration in an extracardiac conduit fontan circulation - Anil K Singhi; Sivakumar Kothandum (Annals of Pediatric Cardiology, 2016)
Failing Fontan physiology in univentricular hearts manifest with protein-losing enteropathy, plastic bronchitis, low cardiac output, and recurrent effusions. Transcatheter creation of fenestration in a failing Fontan may be useful in alleviating the symptoms by improving the cardiac output. It is traditionally achieved by puncturing through the conduit from femoral or jugular venous access. In the absence of good venous path, transhepatic access provides a direct route for needle puncture of the conduit. If marked intimal ingrowth into the conduit results in increasing rigidity and makes the conduit nonyielding, alternative approaches may be needed. A successful creation of pulmonary artery to atrial roof communication through the potential space of transverse sinus using a covered stent is presented.